A free education policy research in Indonesia public senior high school: The evaluation with context input process product model application - Mukodas, Ali; Boeriswati, Endry; Sujanto, Bedjo (International Journal of Innovative Research and Scientific Studies, 2025)
This research evaluates the school operational assistance fund as Indonesian educational funding through the application model. Qualitative research methods were conducted on 10 public senior high schools in Jakarta, Indonesia. Data collection was conducted through content analysis, focus group discussions and interviews. The findings of this study show that in this context, schools understand the legal basis and conduct socialization related to education funding provided by the government. In the input aspect, the school needed to prepare a decree to create an education fund management team according to the existing technical guidelines. Schools also had problems when inputting data into the system provided by the government. As for the process aspect, it was found that the timing of the distribution of school operational assistance funds was not related to the existing regulations. In addition, schools did not have internal supervisors. The implications of this research for education agencies in Indonesia are to pay attention to the suitability of the implementation of education funding with the existing guidelines. It is necessary to evaluate the implementation of the school operational assistance funds policy to improve the quality of education in Indonesia in the coming year.